De-Democratisation and Rising Inequality: The Underlying Cause of a Worrying Trend. Issue 3 (3rd July 2018) - Freeman, Dena
Abstract : This article is concerned with the question of why economic inequality has increased so dramatically in recent decades and what can be done about it. It suggests that the fundamental cause of the recent rise in economic inequality, underlying all the more proximate factors, is a major process of de-democratisation that has taken place since the 1970s, which has increased the political representation of capital while reducing that of labour. The article pulls together a wide range of research from different disciplines in order to decisively show the ways in which economic governance has been de-democratised in this period. This analysis has important consequences with regard to policy attempts to reduce inequality and suggests that these must focus not on technical issues but on ways to strengthen democracy. And if the dynamics of de-democratisation are fundamentally global, then solutions must also be global. These conclusions are in stark contrast with current academic and policy approaches which tend to focus on technical, rather than political, solutions, and which focus overwhelmingly at the national, rather than the global, level. This article thus calls for a major rethinking of the causes of rising inequality and the policy changes needed to reduce it.